Crowdfunding platforms for renewable energy investments: an overview of best practices in the EU - De Broeck, Wouter (International Journal of Sustainable Energy Planning and Management, 2018)
This paper takes a closer look at EU crowdfunding platforms offering investment in renewable energy (RES) projects, how they are exposed to an lead with investor risk. We analyze the platforms’ business model and the resulting risk types, as well as their assessment, mitigation and communication based on an in depth document review and on a survey taken among the platform’s representatives. The resulting overview shows that RES-crowdfunding activity thrives on stable long term policy support schemes for small and medium scale projects, as well as on comprehensive financial regulation that exempts crowdfunding from classic financial service regulatory obligations. When combining the offered financial instruments and underlying RES-projects, a considerable exposure to credit risk can be verified. Risk awareness among platforms can be considered high. However, confidence in the investor’s capability to deal with risk is high as well.